Bird Species Based on Tree Height Perched in the Liwa Botanical Garden, West Lampung Regency - Bagus Susilo Putra; M Kanedi; Nuning Nurcahyani; G. Nugroho Susanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2022)
Birds are one of the most diverse animals in the world, especially in Indonesia. Liwa Botanical Garden located in Pekon Kubu Perahu, Balik Bukit District, West Lampung Regency, is a conservation area with the theme of conservation and development of ornamental plants, representing the flora of Southern Sumatra. This research is a continuation of the collaboration between the Department of Biology and Balitbang UPTD Liwa Botanical Garden, West Lampung Regency. The presence of birds in the Liwa Botanical Garden is also a bioindicator of biodiversity for the environment in this area. By maintaining the presence of birds in the Liwa Botanical Garden means protecting their habitat and existing plants. The purpose of this study was to determine the species of birds based on the height of the perched trees in the Liwa Botanical Garden and the abundance of their species. The method used in this research is the point count with the observation time for 9 days in the morning and evening at the height of the tree in 3 different observation stations. Birds on KRL are mostly found on perches at an altitude of 2 - 7 meters, in the category of shrubs and trees, there are 19 out of 25 bird species found. The highest Relative Abundance Index (IKR) was Collocalia esculenta at 39.91% and the lowest IKR value was 7 bird species, each with 0.14% value. The conservation status of the 25 bird species based on IUCN is Least Concern (LC) and based on CITES there is one species that is included in Appendix II, namely Ictinaetus malayensis while based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No. P.20 / MENLHK / SETJEN / KUM.1 / 6/2018 there is one bird species that is included in the protection, namely species Ictinaetus malayensis.